Analisis Kecacatan Crude Palm Oil (CPO) Menggunakan Metode Quality Control Circle (QCC) di PT. Ujong Neubok Dalam - Miska Arlita; Nissa Prasanti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
Palm oil is used in various industrial players because it has a fairly high economic value. The palm oil processing industry is a very important industry. PT. Ujong Neubok Dalam is a plantation company that is directly involved in planting, maintaining and processing oil palm into Crude Palm Oil (CPO). Supply of raw materials is obtained from the company's own plantations and from third parties with a capacity of 30 tons/hour. During the processing of Crude Palm Oil, several problems occurred. The increase in the level of Free Fatty Acid (FFA) and the level of water content (Moisture) which are outside the company's standard threshold. The standards set by the company PT. Ujong Neubok Dalam for a maximum of 5% Free Fatty Acid, a maximum moisture content of 0.5%, and a maximum dirt content of 0.05%. A total of 103 samples of CPO were tested for 30 consecutive days, found that 90 samples exceeded the FFA threshold, and 51 samples exceeded the moisture content threshold. The application of the Quality Control Circle (QCC) method in reducing the number of defects in this study, it is known that the root of the problem is human factors, machine factors, raw materials used, method factors and work environment factors.